Epidemiology of chronic liver diseases in the USA in the past three decades. Issue 3 (31st July 2019) - Younossi, Zobair M; Stepanova, Maria; Younossi, Youssef; Golabi, Pegah; Mishra, Alita; Rafiq, Nila; Henry, Linda
Abstract : Objective: Given significant advances in treatment of viral hepatitis and the growing epidemic of obesity, the burden of the different types of liver diseases in the USA may be changing. Our aim was to assess the shift in the prevalence of different liver disease aetiologies in the USA over the past three decades. Design: National Health and Nutrition Examination Surveys (NHANES; cross-sectional 1988–1994 and 1999–2016) were used. Results: A total of 58 731 adults from NHANES (1988–2016) were included. Over the study period, the prevalence of chronic hepatitis B and alcoholic liver disease remained stable: 0.3%–0.4% and 0.8%–1.0%, respectively (p>0.05). The prevalence of chronic hepatitis C decreased nearly twofold: 1.6% in 1988–1994 to 0.9% in 2013–2016 (p=0.03). In contrast, the prevalence of non-alcoholic fatty liver disease (NAFLD; by US-Fatty Liver Index) increased from 20.0% (1988–1994) to 28.3% (1999–2004) to 33.2% (2009–2012) and 31.9% (2013–2016) (p<0.0001). Furthermore, steady increases were observed in the rates of obesity (22.2% in 1988–1994 to 31.0% in 1999–2004 to 38.9% in 2013–2016), type 2 diabetes mellitus (T2DM) (from 7.2% to 8.2% to 13.5% same years), insulin resistance and hypertension (all p<0.0001). Yearly trend analyses showed that the only LD with consistently increasing prevalence was NAFLD (trend p=0.01). Multivariable regression analysis showed that obesity (OR 10.4; 95% CI 9.5 to 11.3) and T2DM (OR 3.7; 95% CI 3.2 to 4.2) were the major independent predictors of NAFLD. Conclusions: Over the past 30 years in the USA, NAFLD is the only liver disease with growing prevalence, synchronous with the increasing rates of obesity and T2DM.